Agency Costs of Socialistic Internal Capital Markets: Empirical Evidence from China - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2009)
This study provides empirical evidence of agency costs in socialistic internal capital markets. Listed Chinese companies are required to disclose the amount of resources that are reallocated to other firms of the parent company, which provides us with a direct measure of the socialistic subsidization of weak member firms by strong member firms within a business group. We hypothesize that in strong member firms, managerial compensation is less sensitive to firm performance because cross-subsidization increases the noise in performance measures. We also hypothesize that the agency costs of strong firms are positively associated with the amount of resources that are reallocated because of low pay-performance sensitivity and a low incentive to work hard. We document empirical results that are consistent with these two predictions.